Ethics, Trust, and Adoption: A Literature Review on Student Perceptions of Generative AI in Higher Education - Sari, Annisa Wulan (Universitas Komputer Indonesia, 2025)
The rapid emergence of Generative Artificial Intelligence (GenAI) has sparked a paradigm shift in higher education, placing students at the intersection of technological innovation and ethical ambiguity. This study provides a qualitative systematic review of existing literature to explore the intricate relationship between ethics, trust, and adoption in student perceptions of GenAI. Utilizing a thematic synthesis approach, the research analyzes diverse academic studies to identify recurring patterns in how students navigate these tools. Findings reveal that while GenAI is highly valued for its ability to enhance productivity and personalized learning, adoption is significantly hindered by